The Effect Of Total Quality Management (TQM) and Product Innovation Toward Competitive Advantages - Seftya Dwi Shinta; Levy Oktridarti; M. Imron Rosyadi (Penerbit Jurnal Indonesia, 2024)
This study aims to provide empirical evidence of the Effect of Total Quality Management (TQM) and Product Innovation on Competitive Advantage in the of SMEs food products and crafts typical city of Bengkulu.The data used in this study are primary data, obtained by distributing questionnaires. The sample in this study was 37 SMEs food products and crafts typical city of Bengkulu who had opened and had been operating for at least 5 years. The analysis technique uses the assistance of the SmartPLS 3.0 program. The results showed that Total Quality Management (TQM) contributes to Competitive Advantage and Product Innovation does not conflict with Competitive Advantage.